Effects of aerobic exercise on the regulation of mitochondrial carrier homolog-2 and its influence on the catabolic and anabolic activity of lipids in the mesenteric adipose tissue of obese mice - de Melo, Diego Gomes; da Cruz Rodrigues, Vivian Cristina; de Sá Pereira, Gustavo José; de Campos, Thais Dantis Pereira; dos Santos Canciglieri, Raphael; Pauli, José Rodrigo; da Silva, Adelino Sanchez Ramos; da Costa Fernandes, Célio Junior [UNESP]; de Moura, Leandro Pereira (Elsevier, 2024)
The aim was to understand the direct impact of aerobic short-term exercise on lipid metabolism, specifically in regulating the mitochondrial carrier homolog 2 (MTCH2) and how it interferes with lipid metabolism in mesenteric adipose tissue. Swiss mice were divided into three groups: control, sedentary obese, and exercised obese. The obese groups were induced into obesity for fourteen weeks of a high-fat diet, and the trained submitted to seven aerobic exercise sessions. The exercise proved the significant increase of the pPerilipin-1, a hormone-sensitive lipase gene, and modulates lipid metabolism by increasing the expression of Mtch2 and acetyl Co-A carboxylase, perhaps occurring as feedback to regulate lipid metabolism in adipose tissue. In conclusion, we demonstrate, for the first time, how aerobic physical exercise increases Mtch2 transcription in mesenteric adipose tissue. This increase was due to changes in energy demand caused by exercise, confirmed by observing the significant reduction in mesenteric adipose tissue mass in the exercised group. Also, we showed that physical exercise increased the phosphorylative capacity of PLIN1, a protein responsible for the degradation of fatty acids in the lipid droplet, providing acyl and glycerol for cellular metabolism. Although our findings demonstrate evidence of MTCH2 as a protein that regulates lipid homeostasis, scant knowledge exists concerning the signaling of the MTCH2 pathway in regulatingfatty acid metabolism. Therefore, unveiling the means of molecular signaling of MTCH2 demonstrates excellent potential for treating obesity.
Keywords: Aerobic training; Inflammation; Mesenteric adipose tissue; Mitochondria; Obesity